Analysis of Microalgae Growth Based on Availability of Nutrients in Freshwater - Mainisa; Saiful Adhar; Muliani; Fendi Saputra; Sakinah Hsb (LPPM Universitas Malikussaleh, 2022)
Microalgae have the potential to developed into medicinal products, wastewater treatment, food and energy products. Indonesia is a tropical country has the potential to produce microalgae. The growth of microalgae was influenced by several factors, the main factors is nutrition. This study aims to produce a pattern of mathematical relationships between microalgae growth and nutrient availability of the Laut Tawar Lake. Data collection was carried out for 30 days with a frequency of 7 days at 7 stations. Furthermore, the analysis was carried out to obtain concentration values of nitrate, phosphate and chlorophyll-a. Nitrate concentrations during the study ranged from 310-430 µg/L. The lowest average nitrate concentration was found at Station 4, which was 330 ± 34.64 µg/L and the highest was found at Station 3, which was 396.67 ± 41.63 µg/L. Phosphate concentrations during the study ranged from 18 – 22 µg/L. The highest phosphate concentrations were found at Station 1 and Station 6, which were 20.67 ± 0.58 µg/L and 20.67 ± 1.53 µg/L, and the lowest were found at Station 3, which were 19.00 ± 1.00 µg/L. The concentration of chlorophyll-a ranges from 5 – 12 µg/L. The highest average concentration of chlorophyll-a was obtained at Station 6, which was 10.00 ± 1.00 µg/L and the lowest was found at Station 3, which was 7.00 ± 2.00 µg/L. In conclusion, increasing nitrate in the Lake Laut Tawar did not increase microalgae biomass, microalgae species in that habitat were influenced by nutrient phosphate.